Legal Injustice in the Perspective of Pancasila: Various Recent Developments in Indonesia - Mutiah, Novia Isro’atul (Faculty of Law, Universitas Negeri Semarang, 2023)
Law enforcement in Indonesia has been regulated in the 1945 Constitution paragraph (1) of the 1945 Constitution where everyone is treated equally before the law without any distinction. As stated in the 5th Pancasila precept which reads: